2022
DOI: 10.1242/dmm.049394
|View full text |Cite
|
Sign up to set email alerts
|

Serum inflammatory cytokines as disease biomarkers in the DE50-MD dog model of Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a fatal muscle-wasting disease, caused by mutations in the dystrophin gene, characterised by cycles of muscle degeneration, inflammation and regeneration. Recently, there has been renewed interest specifically in drugs that ameliorate muscle inflammation in DMD patients. The DE50-MD dog is a model of DMD that closely mimics the human DMD phenotype. We quantified inflammatory proteins in serum from wild-type (WT) and DE50-MD dogs aged between 3 and 18 months, to identify bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…To characterise the phenotype of the DE50-MD model, we conducted an extensive natural history study, monitoring disease progression longitudinally over 18 months via multiple complementary approaches (including the muscle physiology measurements described here). This work recently concluded, and results of other investigations suggest that the model exhibits disease progression comparable to that seen in young human patients with DMD: covering the period from first symptomatic manifestation (at approximately 3 years of age) to before loss of ambulation (typically between 10 and 12 years of age) ( Hildyard et al, 2018a ; Riddell et al, 2021 , 2022 ; Hornby et al, 2021 ). Although magnetic resonance imaging (MRI) measurements of DE50-MD dogs muscle volumes did not differ from WT dogs at 3 months of age, the volumes were significantly smaller in DE50-MD dogs at 6 months of age and onwards (except for the cranial sartorius, as discussed above; Hornby et al, 2021 ).…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…To characterise the phenotype of the DE50-MD model, we conducted an extensive natural history study, monitoring disease progression longitudinally over 18 months via multiple complementary approaches (including the muscle physiology measurements described here). This work recently concluded, and results of other investigations suggest that the model exhibits disease progression comparable to that seen in young human patients with DMD: covering the period from first symptomatic manifestation (at approximately 3 years of age) to before loss of ambulation (typically between 10 and 12 years of age) ( Hildyard et al, 2018a ; Riddell et al, 2021 , 2022 ; Hornby et al, 2021 ). Although magnetic resonance imaging (MRI) measurements of DE50-MD dogs muscle volumes did not differ from WT dogs at 3 months of age, the volumes were significantly smaller in DE50-MD dogs at 6 months of age and onwards (except for the cranial sartorius, as discussed above; Hornby et al, 2021 ).…”
Section: Introductionsupporting
confidence: 66%
“…Conducting pre-clinical trials in large animal models has many practical and financial challenges. Findings from this paper and others ( Hornby et al, 2021 ; Riddell et al, 2021 , 2022 ; Hildyard et al, 2022 ) characterising the DE50-MD model have indicated that an n of six dogs per genotype would be optimal for a select panel of biomarkers with high statistical power to detect a phenotypic improvement in response to treatment. ECD would thus be an excellent addition to this panel of biomarkers for future pre-clinical trials in the DE50-MD model.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We firstly described the inflammatory state of these patients, focusing on prevailing macrophages phenotype and on their secretory activity by studying the released cytokine profile. In literature, it has been already reported that inflammation is a typical feature of DMD; in particular, high serum levels of TNF-α, IL-6, IL-7, and other pro-inflammatory molecules have been described [ 53 ]. In accordance, we observed an elevated release of pro-inflammatory cytokines IL-6 and IFN-γ by DMD-associated macrophages.…”
Section: Discussionmentioning
confidence: 99%